The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/curroncol29070353
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Markers of Body Image Concerns in Patients with Head and Neck Cancer: A Prospective Longitudinal Study

Abstract: (1) Background: Patients and survivors of head and neck cancer (HNC) are at a high risk of developing body image concerns. Despite the prevalence of body image concerns in patients with HNC, there is a lack of longitudinal research exploring the wide array of its associated determinants. The current longitudinal study examined the determinants and longitudinal course of body image dissatisfaction in patients with HNC. (2) Methods: Patients participated in Structured Clinical Interviews and self-administered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…Body image was defined as an individual’s subjective thoughts and perceptions of their physical appearance. 23 The levels of body image were assessed using BIS, a brief instrument for measuring body image changes in cancer patients. In the present study, the mean score of BIS was 5.419, with a prevalence rate of 11.8% for body image disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Body image was defined as an individual’s subjective thoughts and perceptions of their physical appearance. 23 The levels of body image were assessed using BIS, a brief instrument for measuring body image changes in cancer patients. In the present study, the mean score of BIS was 5.419, with a prevalence rate of 11.8% for body image disorder.…”
Section: Discussionmentioning
confidence: 99%
“… 55 , 56 Body image disorder can cause social alienation, which leads to higher rates of morbidity and mortality, having a satisfactory perceived body image contributes to better treatment and health outcomes and a better ability to deal with the disease. 23 Compared to other symptoms, body image disorder was rarely discussed between clinicians and survivors with colorectal cancer. 57 Hence, medical workers should also pay specific attention to those patients with body image concerns, tailor communication and take appropriate psychological interventions (eg, psychoeducation about the cognitive model of body image, cognitive-behavioral therapy on building a renewed image after cancer treatment) 58 accordingly, so as to help them correct wrong cognition, promote psychological adjustment, and contribute to good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, limited data from two prospective cohort studies suggest that pre-treatment depression is not a risk factor for HNC-related BID, that BID develops temporally prior to depression in patients for whom the conditions co-occur. 13,43 Additional research is therefore necessary to disentangle the temporal relationship between changes in depression and BID among HNC survivors following BRIGHT. Shame, stigma, and social isolation are all important, if understudied, psychosocial outcomes for HNC survivors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent systematic review of older breast cancer survivors found that older women, particularly those who are post-menopausal, may be less affected by changes to their appearance following breast cancer treatment (Davis et al, 2020 ). In addition to these variables, other socio-demographic and clinical factors which have been demonstrated to affect the relationship between body image and wellbeing following cancer treatment, include gender, marital status, income, education level, cancer stage, treatment type, and many other such variables (Rezaei et al, 2016 ; Albert et al, 2022 ). This demonstrates the need for a nuanced understanding of the complex inter-relationship between body image and clinical, demographic, functional, and psychosocial variables.…”
mentioning
confidence: 99%